Phytochemical Assay and Antiplatelet Activity of Fractions of Velvet Bean Seeds (Mucuna pruriens L.) - WIDOWATI, WAHYU; RATNAWATI, HANA; RUSDI, UDJU DJUNAEDI; WINARNO, WAHYU; IMMANUEL, VICTOR (HAYATI Journal of Biosciences, 2010)
Platelet aggregation is an important factor contributing to the formation of thrombus due to an uncontrolled blood clotting. An antiplatelet agent is a compound which decreases platelet aggregation and inhibits thrombus formation. The objectives of this study were to determine the class of compound employing phytochemical assay and to determine the in vitro antiplatelet activity of four fraction, namely hexane, ethyl acetate, butanol, and water fractions of velvet bean seeds (Mucuna pruriens L.) using epinephrine (EPN) as agonist of platelet aggregation. The antiplatelet activities were tested in human platelet rich plasma with hyperaggregation. To determine the activities, EPN was arranged at 4 level of concentrations (300, 150, 75, and 30 μM), and antiplatelet agents were at 500 µg/ml. The results indicated that ethyl acetate, butanol and water fraction contained high flavonoids and moderate phenols. The water, butanol and ethyl acetate fractions of velvet bean seeds exhibited potential inhibition of EPN-induced platelet aggregation at all concentrations. The strongest antiplatelet agent was water fraction and had the same antiplatelet activity as aspirin at level 150, 75, and 30 μM of EPN. Butanol fraction had the same antiplatelet activity as aspirin at the lowest EPN (30 μM).